Realization of optimization design of electromechanical integration PLC program system based on 3D model - Zhang Lili; Zhang Chuanbao; Wang Peng; Shabaz Mohammad; M. G. Skanda; C. Vijayalakshmi; Kishore Kakarla Hari (Nonlinear Engineering, 2023)
A three-dimensional simulation model of the electromechanical control system was built using the fuzzy control proportional–integral–derivative (PID) adjustment algorithm after an automatic electromechanical control system based on programmable logic controller (PLC) technology was optimized to achieve the practical use of electromechanical program control. First, the hardware of the electromechanical control system is discussed and designed. The findings demonstrate the viability of the mechanical and electrical integration PLC program optimization solution based on three-dimensional (3D) model. The system has a higher control and management efficiency, which is 30% greater than that of the conventional system. The mechatronic manufacturing system’s continuous operation efficiency enhancement can significantly lower the investment costs and boost the financial gains of industrial organizations. Traditional systems have a control and management efficiency of around 30%, but automatic electromechanical control systems based on PLC technology and created using 3D models have a control and management efficiency between 60 and 70%.